An initiative towards sustainability in the petroleum industry: A review. (2021) - Bathrinath, S.; Abuthakir, N.; Koppiahraj, K.; Saravanasankar, S.; Rajpradeesh, T.; Manikandan, R.
Abstract: Rapid industrialization has affected the environment to a large extent. Degradation of the environment has altered the biodiversity's nature, resulting in loss of ecosystem and raising the temperature. Because of the adverse environmental impact, the industrial community faces a wide level of criticism from society. Pressure from society forces the industrial community to adopt sustainable manufacturing practices. Although sustainable manufacturing practice offers a wide range of benefits, there are several difficulties faced by the industrial community in adopting sustainability. One of the industrial sector facing societal pressure is the petroleum industry. The petroleum industry is facing challenges in all three spheres of sustainability, i.e., social, economic, and environmental. This study provides an overview of the challenges related to the petroleum industry. The outcome of the study will benefit the research scholar and policy makers involved in sustainability assessment.